2020
DOI: 10.1093/jjco/hyaa176
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and surgical outcome of soft tissue sarcoma with malignant fungating wounds

Abstract: Objective Malignant fungating wounds are ulcerating tumors that infiltrate the overlying skin. Little evidence exists regarding the prognosis or treatment of malignant fungating wound in soft tissue sarcoma. This study aimed to reveal the prognosis and outcome of surgical treatment of malignant fungating wound in soft tissue sarcoma. Methods We retrospectively reviewed 26 patients with malignant fungating wound in high-grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…In addition to the postoperative survival rate, clinicians are increasingly concerned about the higher recurrence rate and complications caused by limb salvage procedures, as these are associated with a poorer prognosis ( 9 , 10 , 30 ). Some studies have reported no significant difference in the incidence of local recurrence of sarcoma among patients who underwent LSS and amputation ( 8 , 29 ). However, several other studies have implicated LSS with a higher incidence of local recurrence and overall complications ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the postoperative survival rate, clinicians are increasingly concerned about the higher recurrence rate and complications caused by limb salvage procedures, as these are associated with a poorer prognosis ( 9 , 10 , 30 ). Some studies have reported no significant difference in the incidence of local recurrence of sarcoma among patients who underwent LSS and amputation ( 8 , 29 ). However, several other studies have implicated LSS with a higher incidence of local recurrence and overall complications ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of sarcoma patients is evolving with the development of multimodality therapy, and advances in imaging techniques and the use of neoadjuvant chemotherapy have resulted in a greater frequency of limb salvage procedures ( 12 , 28 ), which is consistent with our results in this study. Several small samples or single-center clinical cohort studies have shown that LSS had a better prognosis than amputation among patients with EBST sarcomas ( 13 , 29 ). In addition to the postoperative survival rate, clinicians are increasingly concerned about the higher recurrence rate and complications caused by limb salvage procedures, as these are associated with a poorer prognosis ( 9 , 10 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, patients with MWs from STS were older (mean age: 65-73 years), and presented with higher grade, higher stage, and higher proportion of metastases (20-33%) compared to those without MWs (15)(16)(17)(18). When the lesions are large, possibly requiring skin reconstruction, limb salvage was sometimes difficult, leading to a high rate of amputation (13-33%) (15)(16)(17)(18). Although resection of the tumor can control the symptoms associated with MWs, previous studies reported high rates of surgical site infection (SSI) as much as 26-42% (15,18).…”
Section: Introductionmentioning
confidence: 90%
“…MWs have some oncologic features in STS; thus, it is important to manage both oncologic and infectious problems. In previous reports, patients with MWs from STS were older (mean age: 65-73 years), and presented with higher grade, higher stage, and higher proportion of metastases (20-33%) compared to those without MWs (15)(16)(17)(18). When the lesions are large, possibly requiring skin reconstruction, limb salvage was sometimes difficult, leading to a high rate of amputation (13-33%) (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation